PRO-KONTRA PEMAHAMAN GERAKAN ANTI-BID’AH KELOMPOK SALAFI - Fauzun Jamal (JURNAL INDO-ISLAMIKA, 2018)
The anti-bid'ah doctrine that has been brought up by Salafi groups in Indonesia is not easily accepted by other Islamic groups. Bid'ah is understood by the salafi movement as something new or made up in a religion that does not have the example of the Prophet Muhammad. Some Islamic groups that are not fully in line with this understanding are traditionalist Islamic groups, Sufis and jama'ah tabligh. Not a few religious practices that are usually carried out by them are categorized as heretical and even heretical by the Salafi Movement. Puritanical religious ideas and tend to be radical with the idea of returning to the Koran and al-Sunnah, pure monotheism, without madzhab and ijtihad sometimes in the realm of application creates friction in the community. Several opinions from the scholars expressed in this study, especially from the salafi group. This study found the inconsistency of the Salafi group towards their anti-bid'ah principles and their application. This can be traced from the principle of returning to the text by not functioning ijtihad, qiyas and takwil. This research also explores various literature related to differences in understanding of heresy between salafi groups and the factors that make them different in responding to new practices in religion, especially what is called bid'ah hasanah.